Pathways to a knowledge society: A conceptual approach for changloon’s transformation - Ismail, Russayani; Misiran, Masnita; Md Yusof, Zahayu; Mahat, Nor Idayu (Community Service for Sustainable Community Journal, 2025)
Background: The pursuit of a knowledge society in rural Malaysia represents a transformative vision of development, emphasizing innovation, inclusivity, and sustainable growth. This article introduces a conceptual framework for transitioning Changloon, a rural town, into a knowledge society over a ten-year timeline. Anchored by Universiti Utara Malaysia’s (UUM) leadership, the framework integrates education, community engagement, technology adoption, and sustainable practices across four key pillars: waste transformation, tourism transformation, knowledge transformation, and social transformation. Methods: Using the Living Lab approach, the project fosters real-time experimentation and feedback, ensuring sustainable and practical solutions. Findings: The Changloon Transformation Project (CTP) utilizes the Living Lab methodology to address socio-economic challenges and transition Changloon into a knowledge society, integrating waste, tourism, knowledge, and social pillars. Its proximity to Universiti Utara Malaysia (UUM) enhances the project's potential, ensuring community-driven, sustainable solutions. Conclusion: Despite the challenges of behavioral change and innovation among disadvantaged groups, the project addresses these issues through skills development, financial literacy, and mentorship programs. CTP serves as a replicable model for other rural communities, demonstrating how local strategic solutions and partnerships can create resilient and inclusive communities. Novelty/Originality of this article: This research contributes to the field by introducing a holistic knowledge society framework tailored to rural, integrating waste and tourism transformation as key drivers of economic and social resilience.